Teaching work and impact the pandemic in mental health (Research, Society and Development, 2022)
Objective: to analyze the impact of COVID-19 on the mental health of university professors at a higher education institution in Serra da Ibiapaba. Methodology: it consisted of a bibliographical research of texts considered relevant for the same, in addition to a field research, through the application of a questionnaire using google forms, of a qualitative nature, with the professors of a higher education institution in Serra da Serra. Ibiapaba, totaling 13 (thirteen) responses. Results: from this study, it is concluded that most teachers suffered from the pandemic and had some impact on mental health. The pandemic scenario made teachers increase their working hours and with it the level of stress, even with the support in the new teaching transactions made available by the institution.